Optimization of molding parameter effect to warpage of car dashboard based on plastic flow simulation software - Mohd Zahiruddin, Azri (2009)
This thesis present about the optimization of molding parameter effect to warpage of car dashboard based on plastic flow simulation software. The objective of this project is to study, analyze, and optimize the parameters that effect to warpage with using plastic flow simulation software. This project using the manual measurement after the original method using 3D scanner cannot be done because of the technical report. The measurement uses the tools from the Faculty of Mechanical Engineering Laboratory such as ruler, vernier calliper, threads, and protractor. Then, draw the dashboard in SolidWork 2008. Using MoldFlow Plastics Insight (MPI) 5.0 software, the injection molding parameters are optimized to get the best parameters to minimize warpage. The small changes of molding parameters will give higher impact to the plastic characteristics. The comparison between the types of analysis will be made. The comparison is between the deflections, fill times, and volumetric shrinkage including air traps and weld lines. As the conclusion, the changes of molding parameters will affect the warpage of the car dashboard.